A user-friendly tool to assess management plans for European eel fishery and conservation. (February 2015) - Schiavina, Marcello; Bevacqua, Daniele; Melià, Paco; Crivelli, Alain J.; Gatto, Marino; De Leo, Giulio A.
Abstract: The European eel Regulation EC 1100/2007 establishes measures to recover the European eel stock. The Regulation requires Member States to guarantee a spawner escapement ≥40% of pristine levels by reducing eel mortality. The complexity and plasticity of eel life history make it difficult to assess the effectiveness of alternative management options, and tools allowing decision makers and fishermen to quickly assess the effectiveness of proposed management scenarios are urgently needed. We used state-of-the-art knowledge to develop a user-friendly simulation software allowing users to evaluate if current management policies meet the conservation target and evaluate the expected performances (spawner escapement and fishing yield) of alternative management scenarios. The software relies upon a demographic model explicitly accounting for the most relevant features of eel demography and has default settings for specific geographical areas and water systems. We demonstrate the software by exploring a variety of management plans in three European water systems. Highlights: We developed a user-friendly software to simulate European eel demographic dynamics The software is based on a set of models describing specific life history traits The software allows a quick screening assessment of alternative management plans We demonstrate the software by applying it to three European eel stocks